An Analysis of the Instillation of Nationalism Values in Fourth-Grade Students’ Instructional Textbooks (Literasi Nusantara, 2026)
This study aims to analyze the instillation of nationalism values ​​in the Pancasila Education Textbook for grade IV elementary school published by Buku Ajar X, identify the values ​​contained, and evaluate the extent to which the presentation reflects the diversity of Indonesian culture. The research method uses a descriptive qualitative approach, which examines texts, discourse practices, and social practices. Data were obtained through documentation of texts, illustrations, and learning activities in the textbook, which were analyzed based on the following indicators: 1. Love for the homeland 2. Mutual cooperation 3. Tolerance 4. Proud to be Indonesian. The results of the study indicate that the textbook contains nationalistic values, but the delivery is more implicit through stories, illustrations, and activity instructions. The most dominant value is love of the homeland, which is displayed through the flag ceremony as a symbol of the state, and school discipline. Mutual cooperation is represented through collective activities such as cleaning the classroom or community service, while tolerance is depicted through illustrations of harmony between religious communities, for example, Balinese pecalang who maintain security when Muslims perform worship. Pride as an Indonesian nation is shown through cultural parades, traditional dances, and traditional clothing. Although Indonesia's cultural diversity is present in the textbook, its representation is still symbolic without in-depth explanation.
Keywords: Textbooks; Nationalism; Critical Discourse Pancasila Education; Elementary Schools